Exploring the relationship of threshold concepts and Hodges' model of care from the individual to populations and global health - Peter Jones (Universidad de Santander, 2017)
Through academia, professional disciplines seek - whenever possible - to base their actions on theory rather than fact and historical practices. This serves to improve certainty and place curricula, research, and practice on the best footing in terms of knowledge and quality. This emphasis extends to the workplaces in which professionalised disciplines are learned and practised. In healthcare, great importance is placed upon evidence-based findings to support clinical practice. Although subject to ongoing debate, the quality of research is assessed against a yardstick that culminates in a 'gold-standard' of clinical trials and systematic reviews. What healthcare professionals do, should, whenever possible, be based upon evidence, not ritualised practices and missives, such as "I was trained this way" and "This is how we do things here". How to cite this article: Jones P. Exploring the relationship of threshold concepts and Hodges' model of care from the individual to populations and global health. Rev Cuid. 2017; 8(3): 1697-720.  http://dx.doi.org/10.15649/cuidarte.v8i3.464